Evaluation of the Effect of ACC Deaminase and Exopolysaccharides Producing Bacteria in Maize (Zea mays) under Heat Stress - Rafi, Amara; Chaudhary, Hassan Javed; Ali, Javed; Kutawa, Abdulaziz Bashir; Amna, Amna; Khan, Misbah; Aslam, Nida; Ur Rehman, Shafiq (Trends in Sciences, 2022)
Heat stress or global warming is a continuous temperature fluctuation that affects the environment and damage plant tissues because of the hormonal imbalances in plants. Yield losses resulting from heat stress are a major threat to global food security. Plant growth-promoting bacteria (PGPB) may be utilized to lessen this loss in yield. PGPB containing aminocyclopropane-1-carboxylic acid (ACC) deaminase activity can enhance plant growth that various abiotic stresses inhibit. This work was conducted to evaluate the effect of ACC deaminase and exopolysaccharides producing bacteria on maize plants grown under heat stress. The stressed plants were kept at 45 °C, while non-stressed plants were grown at a temperature of 28 - 35 °C. In 45 days of the growing period under heat stress, the plant growth and activities were decreased, however, in the presence of PGPB (isolated from soil and plant tissues in Muzaffagarh, Pakistan) containing ACC deaminase activity, the plant activities and biomass were increased compared to their respective control. The ACC deaminase-producing bacteria played a significant role by enhancing the physiological activities of the plants like chlorophyll a and b, carotenoid pigments, and proline content. Enzymatic activities like superoxide dismutase (81 %), peroxidase (57.8 %), and catalase (50.27 %) were increased. The relative water content of the maize plants was increased in Treatment one (T1) with 300, and 200 % for non-heat and heat, respectively, while the control was having 220, and 200 % for non-heat and heat, respectively. Soluble sugar content was improved with T1 having the highest values (4,000 and 5,700 g/mol) for heat and non-heat, respectively. The control was having 900, and 2300 g/mol for heat and non-heat, respectively. The application of ACC deaminase-producing bacteria on maize can help to overcome the adverse effects of heat stress and help the plant to survive under stress condition. HIGHLIGHTS Heat stress is a continuous temperature fluctuation that affects the environment and damage plant tissues because of the hormonal imbalances in plants, and yield losses resulting from heat stress are a major threat to global food security This research work was carried out to assess the effect of ACC deaminase and exopolysaccharides producing bacteria on maize plants grown under heat stress The use of ACC deaminase-producing bacteria on maize can help to overcome the adverse effects of heat stress and help the plant to survive under stress condition GRAPHICAL ABSTRACT